RANCANG BANGUN SISTEM KONTROL PENYIRAM TANAMAN BERDASARKAN SENSOR SOIL MOISTURE DENGAN MENGGUNAKAN ARDUINO - Adhi Cahyono (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
In this era of development, technological development encourages people to continue to think creatively to maximize the performance of existing technology to improve human work in daily life. Almost all activities of human activities use modern technology, ranging from the world of industry, households and even agriculture. In the field of agriculture still has problems, one of which is watering the plants that are still manually. For this reason, it is necessary to think of a plant sprinkler automatically. Where this tool changes the role of humans in the care of plants, namely in terms of watering plants. One of these methods helps human work every day to be more time efficient and practical without having to place it. With this tool, it is expected that farming activities with plant watering systems will automatically be increasingly in demand. Because this tool is made capable of watering plants automatically based on the value of soil moisture detected by soil moisture sensors. With the control system using Arduino as a microcontroller and also the instructor of the water pump.